“Health Belief Model” in the Prevention of Chronic Disease in the Elderly - Lufthiani, Lufthiani; Bukit, Evi Karota; Siregar, Cholina T (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Chronic disease is a non-communicable disease categorized as a long-term disease due to physiological changes in the body in the elderly. Chronic disease can be prevented with a healthy lifestyle and education through the Health Belief Model with the belief that someone takes a series of actions to overcome disease and reduce side effects. This study aims to determine how the effect of the application of the “Health Belief Model” in the Prevention and Health Care of Chronic Disease in the Elderly, which was carried out with a total sample of 100 respondents. The research design used Quasi Experiment with a pre-test and post-test approach with a control group design, a knowledge questionnaire about chronic disease, disease prevention, and health care including pre-test and post-test, used Paired T-Test with knowledge result p-value 0.000 α (α = 0.05) and health prevention and maintenance p-value 0.000 α. (α = 0.05) so it can be concluded that there is an effect of implementing the “Health Belief Model” in the prevention and maintenance of chronic disease health in the elderly.